2018
DOI: 10.1016/j.shaw.2018.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Working Conditions, Job Strain, and Traffic Safety among Three Groups of Public Transport Drivers

Abstract: BackgroundWorking conditions and psychosocial work factors have acquired an important role explaining the well-being and performance of professional drivers, including those working in the field of public transport. This study aimed to examine the association between job strain and the operational performance of public transport drivers and to compare the expositions with psychosocial risk at work of three different types of transport workers: taxi drivers, city bus drivers, and interurban bus drivers.MethodA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
65
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(70 citation statements)
references
References 52 publications
1
65
0
4
Order By: Relevance
“…Job strain, iso‐strain and ERI are measures commonly used to evaluate psychosocial work factors. In one study of 195 taxi drivers from Bogota, Columbia, the mean job strain ratio for taxi drivers was 0.68 (±0.20), which was lower than city bus drivers and intercity bus drivers . In a prior analysis of psychosocial factors and low back pain using our sample of taxi drivers, job strain, iso‐strain and ERI were not associated with low back pain; the mean job strain ratio was 0.49 (±0.15).…”
Section: Introductionmentioning
confidence: 66%
See 1 more Smart Citation
“…Job strain, iso‐strain and ERI are measures commonly used to evaluate psychosocial work factors. In one study of 195 taxi drivers from Bogota, Columbia, the mean job strain ratio for taxi drivers was 0.68 (±0.20), which was lower than city bus drivers and intercity bus drivers . In a prior analysis of psychosocial factors and low back pain using our sample of taxi drivers, job strain, iso‐strain and ERI were not associated with low back pain; the mean job strain ratio was 0.49 (±0.15).…”
Section: Introductionmentioning
confidence: 66%
“…In this study, perceived mental exertion and depression symptoms were found to be associated with job strain, iso‐strain, and ERI. Similarly, job strain was found to be significantly associated with depression in professional drivers, including taxi drivers, in Columbia . Persistent job demands were also explored by Evans both in focus groups (qualitative) and descriptive (quantitative) studies, using the JCQ, in Australian taxi drivers.…”
Section: Discussionmentioning
confidence: 99%
“…The data contains 4 parts: descriptive statistics, bivariate correlations between the study variables, analysis of variance (ANOVA) and Post-Hoc comparisons between drivers classified different quadrants of the JDC model. For further information, it is convenient to read the full article entitled “ Working conditions, job strain and traffic safety among three groups of public transport drivers ”, published in Safety and Health at Work (SHAW) [1] (Useche et al, 2018).…”
mentioning
confidence: 99%
“…However, it can be argued that motorcycle taxi drivers working night shift tended to deal with a much less stressful environment with fewer conflicts and lighter traffic flow. The impact of work-related stress on traffic safety outcomes was evident in previous research [34]. Furthermore, street lighting is generally adequate in Hanoi's urban areas.…”
Section: Discussionmentioning
confidence: 74%
“…An understanding of associations between BMI and crashes among motorcycle taxi drivers will have important implications for the occupational health and safety of these taxi-riders as well as health and safety of the general road users. While occupational health and safety of professional drivers have been the subjects of a growing body of literature [2,[31][32][33][34], there is a lack of research examining associations between BMI and crashes, particularly injury crashes, among motorcycle taxi drivers, as discussed above.…”
Section: Introductionmentioning
confidence: 99%